Mahasantri Sebagai Pelaku Perekonomian di Era Industri 4.0 - Eny Lathifah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2019)
This study aims at the role of Mahasantri in increasing economic potential and obstacles to face the industrial era 4.0. The research method is qualitative interactive with trigulation instruments. The result of the study indicate that mahasantri is very instrumental and able to find solutions to obstacles in increasing economic potential to face the era of industry 4.0.